Thermal energy storage enhancement of latent heat thermal energy storage systems - Low, Zheng Hua (Nanyang Technological University, 2025)
With the pressing need to decarbonize, industries are turning to renewable energy and energy saving technologies in a bid to reduce emissions. Latent Heat Thermal Energy Storage (LHTES) systems is an enabler for waste heat energy storage, solar power storage, district heating and cooling. By tapping on the high latent heat capacity of Phase Change Material (PCM), LHTES systems can store heat energy for later use. An in-depth review of the current state-of-the-art on the application of various metallic fins in several geometries is presented, together with the working and design principle of the application of fins, detailed explanations of key fin parameters, effect of natural convection on LHTES performance, corrosion, and numerical model assumptions. The occurrence of dead zones, the slowest region of LHTES system to melt or solidify, causes non-uniform melting and temperature profile. The location, volume and quantity of dead zones varies depending on the geometry of the LHTES system and location of heat transfer surface. To mitigate the adverse effects of dead zones, metallic fins are employed to achieve thermal penetration into said zones at an early stage to promote more uniform melting and temperature profile. To improve natural convection flow, angled metallic fins were proposed on a side-wall heated LHTES system. Experiment and numerical models were built to investigate the efficacy of angled metallic fins, and to study the combined effects of varying fin length and angle. With respect to horizontal fins, positively inclined fins of +15º and +30º delayed the full melt time by 3.8% and 4.0%, respectively, while negatively inclined fins at -15º and -30º improved the melt fraction difference by up to 5.2%. Three fin lengths corresponding to dimensionless lengths of 0.375, 0.625 and 0.875 were numerically studied together with varying angles. Results indicate that the longest fin with a downward angle of -15º yielded the best improvement in melt time. The study shows that long, downward tilted fins enhance PCM transient melting in a rectangular LHTES and the considerations that go along with these parameters. Apart from applying metallic fins in LHTES systems, varying geometry of LHTES is often an overlooked aspect of improving system performance. Recovery of waste heat from exhaust gases, analogous to heat recovery in Combined Cycle Gas Turbines (CCGT) is an excellent way to improve Gross Turbine Heat Rate (GTHR); enhancing such operations will go a long way in reducing gas consumption and improving efficiency. To increase heat transfer surface area, while maintaining the same PCM volume, protrusion and concave designs were proposed by varying the side wall angles of a rectangular enclosure. The protrusion geometry (133.8º) reduced melt time by 24.9% compared to the baseline rectangular geometry (90º). Application of parallel fins in horizontal annular LHTES systems is a common way to improve melt time. Multiple sectioned parallel fins were proposed to increase fin surface area, without reducing PCM volume (for parallel fin of same volume). A numerical model was built and validated to conduct parameter study on the proposed designs. Two main arrangements, half section (1 split) and quarter section (3 splits) were investigated using an annular LHTES system employing RT42 as PCM. The melt time of proposed designs improved by 64.2% and 4.3%, respectively, when compared to parallel and no fin case. The sections created additional pathways for liquid PCM to flow in the longitudinal direction. Future recommendations call for standardized design parameters for fins in various geometries and wider, system level research, lifetime assessments, partial charge capabilities, for wide spread adoption of LHTES.